MODIFIKASI SPENT BLEACHING EARTH DENGAN WO3 MELALUI PROSES PILARISASI UNTUK UJI FOTODEGRADASI ZAT WARNA METHYLENE BLUE - Rinda Anisyah Putri; Noor Hindryawati; RR. Dirgarini Julia N. S. (PROSIDING SEMINAR KIMIA, 2018)
The Research on modification of Spent Bleaching Earth (SBE) with WO3 has been studied through the process of pillarization for dye photodegradation test of Methylene Blue. This research start from the process of sample preparation, SBE activation using H2SO4, addition of rarasaponin on SBE, pillarization of WO3 on SBE and photodegradation test. DSBE-WO3 was characterized using X-Ray Flouresence (XRF) and X-Ray Diffraction (XRD). XRF analysis of DSBE-WO3 showed an increase in SiO2 composition after activation. The XRD pattern of DSBE-WO3 showed the presence of a WO3 peak. The optimum conditions for photodegradation of methylene blue with DSBE-WO3 were obtained when the 0,02 g of DSBE-WO3, 60 minutes contact time and 100 ppm concentration of methylene blue were used with percent degradation of 95,18%. Keywords: Spent Bleaching Earth, pillarization, WO3, Methylene Blue, photodegradation.